2022
DOI: 10.3389/fneur.2022.874826
|View full text |Cite
|
Sign up to set email alerts
|

Supratotal Resection of Gliomas With Awake Brain Mapping: Maximal Tumor Resection Preserving Motor, Language, and Neurocognitive Functions

Abstract: Gliomas are a category of infiltrating glial neoplasms that are often located within or near the eloquent areas involved in motor, language, and neurocognitive functions. Surgical resection being the first-line treatment for gliomas, plays a crucial role in patient outcome. The role of the extent of resection (EOR) was evaluated, and we reported significant correlations between a higher EOR and better clinical prognosis of gliomas. However, recurrence is inevitable, even after aggressive tumor removal. Thus, e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 74 publications
1
9
0
Order By: Relevance
“…Generally, resection beyond 1-2 cm for contrast-enhanced tumors or 1-2 cm beyond the boundary in Flair images for non-enhanced tumors could be considered acceptable supratotal resection (33). Evidence indicated that supratotal resection might improve EOR and prolong the progression-free as well as OS in glioma patients (34). Our findings also suggested that awake brain mapping enabled surgeons to achieve supratotal resection with favorable neurological and clinical outcomes while preserving the neurocognitive function.…”
Section: Discussionmentioning
confidence: 58%
“…Generally, resection beyond 1-2 cm for contrast-enhanced tumors or 1-2 cm beyond the boundary in Flair images for non-enhanced tumors could be considered acceptable supratotal resection (33). Evidence indicated that supratotal resection might improve EOR and prolong the progression-free as well as OS in glioma patients (34). Our findings also suggested that awake brain mapping enabled surgeons to achieve supratotal resection with favorable neurological and clinical outcomes while preserving the neurocognitive function.…”
Section: Discussionmentioning
confidence: 58%
“…Although gross total resection is generally recommended to improve the prognosis, [ 31 ] striking a balance between tumor clearance and functional preservation remains a major concern, since determining the optimal resection margin is difficult. [ 32 ] Therefore, the extent of healthy tissue co‐resected during this process was evaluated through the Ki‐67 staining. Figure S16c (Supporting Information) illustrates examples of tumor resections guided by saline, indocyanine green (ICG), PLNP, and PLCNP.…”
Section: Resultsmentioning
confidence: 99%
“…One step forward is to achieve a “supra-complete” resection, to remove the PTZ which contains ITC exposing patients to a high risk of recurrence [ 49 , 66 ]. Long-term follow-up after supra-marginal LGG excision has shown a stronger impact on the natural course of the disease [ 27 , 48 , 81 , 82 ]. As a consequence, it has been proposed to consider LGG as remaining “high-risk” even in young patients (<40 years) who have had only a subtotal resection [ 83 ].…”
Section: Predicting Oncological Interindividual Variability and Its C...mentioning
confidence: 99%